Misconceptions on basic electricity of high school physics teachers of Ilocos Sur - Navarro, Mary Grace R. (Vigan City, Ilocos Sur: [s.n.], 2004)
This study primarily aimed to determine the understanding and misconceptions on some situation involving basic electricity of Ilocos Sur High School physics teachers during the school year 2003-2004.
Includes bibliographical references.
CHED-La Union
Keywords: Teachers; Electricity